2017
DOI: 10.22617/brf178794-2
|View full text |Cite
|
Sign up to set email alerts
|

Insurance for Micro, Small, and Medium-Sized Enterprises

Abstract: Small and medium-sized enterprises (SMEs) are a key component of every economy. Studies fill the literature with the importance of SMEs as employment generators, innovators, factors in the supply chains of larger enterprises, and important contributors to gross domestic project.SMEs are also relevant in developed and developing countries alike, bearing in mind that definitions of SMEs differ by the size of the economy. Estimates suggest that more than 95% of enterprises around the world are SMEs, accounting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
4
2
Order By: Relevance
“…insurance) was the least used risk management technique among the SMEs, as the majority of operators/owners were ignorant of the workability of risk transfer mechanism and its financial cost implications on their business operations. Also, the result was contrary to the opinions of Chatterjee, Wehrhahn (2017), who noted that permitting insurers to carefully provide loans to MSMEs could create significant synergies, curtailing distribution costs and creating additional income. Source: Authors' own study.…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation
“…insurance) was the least used risk management technique among the SMEs, as the majority of operators/owners were ignorant of the workability of risk transfer mechanism and its financial cost implications on their business operations. Also, the result was contrary to the opinions of Chatterjee, Wehrhahn (2017), who noted that permitting insurers to carefully provide loans to MSMEs could create significant synergies, curtailing distribution costs and creating additional income. Source: Authors' own study.…”
Section: Resultscontrasting
confidence: 59%
“…Previous studies have shown that enterprises on either small or medium scales are key instruments to the developmental strides of any economy (Abotsi, Dake, Agyepong, 2014;Garg, Makukule, 2015;Terungwa, 2012). Recent studies such as (Abotsi et al , 2014;Ahmed, Abdul-manab, 2016;Chatterjee, Wehrhahn, 2017) have shown that small and medium scale enterprises are the engines to attain the growth objectives of developing countries in terms of mobilising idle funds, being labour intensive, the main source of employment, economic advancement, a revenue-generating source and technology innovation. Estimates, according to Ayyagari, Demirguc-Kunt, Maksimovic (2011), suggested that more than 95% of enterprises around the world were SMEs, accounting for about 60% of the private sector employment.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that business insurance has no influence on profitability of business. However the results differed with some other studies that reported that an insured business was likely to report more profits [40].…”
Section: Resultscontrasting
confidence: 99%
“…Such an innovative approach would navigate the highlighted challenge of inaccessible financing for the segment. The recommendation by Beck & Cull (2014) on innovation in financing approaches was in line with the recommendation by Chatterjee & Wehrhahn (2017) to create innovative products that leverage on pooling of resources. Kadocsa & Francsovics (2011) in their study of SMEs in Hungary conclude that after Hungary's accession to the European Union, the small businesses did not take advantage of the European Union new markets and opportunities due to lack of information.…”
Section: Financial Factors and Financial Performance Of Informal Micro Enterprisesmentioning
confidence: 74%
“…The study further found that a reliable monetary policy had the most impact on business operation among economic policy factors while for the micro economic factors the important ones were cost management, marketing, trade, financing, technical development and production. Chatterjee and Wehrhahn (2015) provide telling statistics on the prominence of SMEs to the global economy -up to 95% of enterprises are SMEs; these account for up to 90% of private sector employment. The proportion of SMEs differs by country with countries such as Japan posting up to 99% of SME representation.…”
Section: Financial Factors and Financial Performance Of Informal Micro Enterprisesmentioning
confidence: 99%